Workshop dan Edukasi Pemanfaatan Herbal sebagai Upaya Peningkatan Kesehatan Keluarga pada Anggota PKK: Workshop and Education on Herbal Utilization to Enhance Family Health for PKK Members - Ebtavanny, Tamara Gusti; Hariadini, Ayuk Lawuningtyas; Firdaus, Favian Rafif; Achmad, Anisyah; Amalia, Thia; Nabilah, Varna Amalia; Fauzan, Evan; Azis, Umar Abdul; Wibowo, Andriani Abigail (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
The Family Welfare Empowerment (PKK) is a community group dedicated to fostering family and societal well-being, with health being one of its key focus areas. PKK members are pivotal in enhancing family immunity, particularly during heightened risk from bacterial, viral, and other infections. The community's preference for traditional medicine, which has been empirically proven to be safe and effective, such as *Andrographis paniculata* (sambiloto) and *Curcuma longa L.* (turmeric), serves as a viable solution for boosting family immunity. This program aimed to provide education and workshops to 50 PKK members in Kendalpayak Village through education sessions, pre-and post-tests, a herbal drink preparation workshop, and follow-up consultations. The education covered topics on the immune system, the definition and application of traditional medicine, and the rational use of herbal remedies. The program results revealed a significant improvement in participants' knowledge, with average pre-test scores of 81.71 rising to 93.90 in post-tests, reflecting a 12.19% increase. Furthermore, the proportion of participants with